Swine dust causes intense airways inflammation in healthy subjects - Larsson, K A; Eklund, A G; Hansson, L O; Isaksson, B M; Malmberg, P O (American journal of respiratory and critical care medicine, 1994)
Fourteen healthy, nonsmoking subjects were exposed to swine dust while weighing pigs for 3 to 5 h in a swine-confinement building. All but one participant was previously unexposed to swine dust. Bronchoalveolar lavage (BAL) was performed and blood samples were drawn before and after exposure. Total dust and endotoxins were measured by air sampling in filter cassettes carried in the breathing zone. The air concentration of endotoxins was 0.6 (range, 0.08 to 1.3) micrograms/m3, and of total dust was 13.5 (range, 5.6 to 24.0) mg/m3. The air concentrations of ammonia, carbon dioxide, and hydrogen sulfide were low. The exposure induced fever in three and malaise and drowsiness in six of the subjects. Compared with preexposure values, a 75-fold increase in neutrophilic granulocytes, a two- to threefold increase in mononuclear cells, and a significant increase in eosinophilic granulocytes were observed in the BAL fluid obtained 1 day (approximately 22 h) after exposure (p < 0.01 for all cell types). The fibronectin and albumin concentrations in the BAL fluid significantly increased (p < 0.01 for both). The number of leukocytes in peripheral blood was almost doubled 6 h after exposure and was still significantly elevated after 1 day. Blood concentrations of orosomucoid and C-reactive protein (CRP) were significantly increased 1 day after exposure. We conclude that exposure to swine dust in a swine-confinement building induces an intense inflammatory reaction in the airways as assessed by BAL. The airway cellular response is characterized by a dramatic increase in neutrophils. The components in the swine dust that cause the reaction are not clear.